1996
DOI: 10.2172/231967
|View full text |Cite
|
Sign up to set email alerts
|

Observations of neutral beam and ICRF tail ion losses due to Alfven modes in TFTR

Abstract: Fast ion losses resulting from MHD modes at the Alfv6n frequency, such as the TAE, have been observed in TFTFt. The modes have been driven both by neutral beam ions, at low BT, and by H-minority ICRF t a i l ions at higher BT. The measurements indicate that the loss rate varies linearly with the mode amplitude, and that the fast ion losses during the mode activity can be significant, e.g. up to 10% of the input power is lost in the worst case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Energetic particle loss resulted from TAE instabilities driven by neutral beam injection and ICRF heating but not by alpha particles (Darrow et al, 1996b). The Occurrence of magnetic fluctuations with different toroidal mode numbers is observed.…”
Section: Iters9-pmentioning
confidence: 86%
See 1 more Smart Citation
“…Energetic particle loss resulted from TAE instabilities driven by neutral beam injection and ICRF heating but not by alpha particles (Darrow et al, 1996b). The Occurrence of magnetic fluctuations with different toroidal mode numbers is observed.…”
Section: Iters9-pmentioning
confidence: 86%
“…These modes were predicted to be driven unstable by energetic particles through wave-particle resonances by tapping the free energy associated with the energetic alpha pressure gradient (Cheng et al, 1989;Fu and Van Dam 1989;Cheng 1991 instabilities, as shown in Fig. 53, can be sufficiently strong to eject a large fraction of the fast particles (Darrow et al, 1996b) and to damage first wall components .…”
Section: A Toroidal Alfvdn Eigenmodesmentioning
confidence: 99%
“…Fast ion losses induced by AEs have been measured in tokamak and stellarator/ heliotron devices with the scintillator-based detectors (Darrow et al 1997;Weller et al 2001;Isobe et al 2006;Darrow et al 2008;García-Muñoz et al 2010;Van Zeeland et al 2011;Ogawa et al 2012). The lost particles measured by the detectors on the tokamaks are mainly trapped particles that were originally counter-passing particles to the plasma current, lost energy due to the interaction with the AEs, and became trapped particles.…”
Section: Fast Ion Lossmentioning
confidence: 99%
“…These instabilities, as shown in Fig. 53, can be sufficiently strong to eject a large fraction of the fast particles (Darrow et al, 1996b) and to damage first wall components .…”
Section: A Toroidal Alfvdn Eigenmodesmentioning
confidence: 93%
“…Fraction of energetic particles power lost from the plasma and the TAE mode amplitude versus the heating power in TFTR discharges. Energetic particle loss resulted from TAE instabilities driven by neutral beam injection and ICRF heating but not by alpha particles (Darrow et al, 1996b).…”
Section: Fig 40mentioning
confidence: 97%